Wind energy and the possibility of investing it in the production of electric energy in the district of Aana and achieving sustainable Development - Al-Dulaimi, Salah Adnan Mejwal (Al-Adab Journal, 2022)
This research deals with renewable energy in general and wind energy in particular, and its importance in producing cheap and clean electric energy for the environment and the possibility of investing it to produce energy, which provides the residents of Anah district and other neighboring districts another source of energy other than energy derived from Haditha Dam, especially the large distances between districts in Anbar Governorate And the small amount of energy received from remote districts, and the study begins with the study problem, hypothesis, study objectives and research between the relationship between energy and sustainable development, in addition to researching the possibilities of eliminating it from wind energy to produce energy, in order to be a model for the rest of the districts of Anbar Governorate and Iraq. The lack of electrical power in Anah district, despite its proximity to the Haditha Dam, which supplies most of the western regions of Iraq and Anbar Governorate. The wind in Anah district enjoys sufficient speed to generate electric power from the wind, as the average wind speed recorded in Anah station exceeds the permissible limit of wind speed to generate electric power, which is (303 m/s and above), taking into account the prevailing wind direction and that the prevailing wind direction It is the west wind.